Інноваційні підходи до вивчення життєтворчості Тараса Шевченка в системі літературної освіти - Бойко, Тамара; Жалко, Тетяна (My University, 2018)
У статті здійснено аналіз актуальних ідей з проблеми використання інноваційних підходів до вивчення життя і творчості Тараса Шевченка в системі літературної освіти. Особливий акцент зроблено на способах втілення інноваційних підходів (форм, методів, засобів навчання) у шкільному курсі української літератури. Доведено, що інноваційна діяльність в освіті – це об’єктивний процес, якого в умовах глобалізації вимагає ринок освітніх послуг. In the article the analysis of actual ideas is carried out on issue of the use of the innovative going near the study of life and creation of Tarasa Shevchenko in the system of literary education. It is marked that the important aspect of research is an attempt to light up importance of application of pedagogical innovations in to educational-educate process of modern school and to offer the interesting forms of work at the study of zhittetvorchesti of Tarasa Shevchenko (lesson-trip, lesson-presentation, lesson-search, videopoetry, fleshmob, to the mine-kvest, rolevi and literary games, senkon, method of projects, reflection, educational discussions and other). The special accent is done on the methods of embodiment of innovative approaches (forms, methods, facilities of studies) in the school course of ukrainian literature. It is well-proven that forming of professional jurisdictions is for introduction of active methods of studies, which provide development of critical thought, are the important element of professional development of pedagogical workers, and innovative activity in education
Keywords: інноваційні підходи; innovative approaches; творчість Тараса Шевченка; літературна освіта; інновація; освітній процес; creation of Tarasa Shevchenko; literary education; innovation; educational process